(3GSJNOGe GdCSGdjH GdcejI aj UfY GdbQGQs - (3eMeO GSeGYjd(B, (3HdGds ((3GdEScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI(B,s, 2005)
(3GdHQeLI GdNWjI(B- (3SdGSd eGQcha(B- (3THcGJ GdGYeGd(B- (3fehPL Gdfbd GdQjGV(B- (3fXQjI GdbQGQ(B- (3fXQjI GdeHGQjGJ(B- (3GdHQeLI GdOjfGejcjI(B.s
Keywords: (3GdHQeLI GdNWjIs; (3HMhK GdYedjGJ(B- (3EJNGP GdbQGQGJs